A new class of fluorogenic thiazolo[2, 3-b]quinazolinone receptor: selective detection towards mercury and hydrogen bisulfate ions in aqueous medium. Issue 53 (11th October 2021) - Mohanta, Prajna Parimita; Devi, Aparna Prabha; Bag, Bhawani Prasad; Pati, Hari Narayan; Behera, Ajaya Kumar
Abstract : Fluorophoric thiazoloquinazoline derivatives were synthesized under microwave assisted one-pot three-component cascade reaction. Owing to their unique structural arrangement, a new bioactive molecular receptor was developed for HSO 4− and Hg 2+ ions. Abstract : A series of fluorophoric and structurally diverse thiazoloquinazoline derivatives were synthesized in a one-pot multicomponent cascade reaction using a microwave irradiation technique. The unique structural arrangement of the synthesized compounds encouraged us to design a new type of bioactive molecular receptor. This receptor interacts with HSO4 − in 1 : 1 and Hg 2+ in 1 : 2 binding stoichiometric ratios resulting in a change in fluorescence as well as absorption spectra in aqueous medium. The ion bonded receptor complex possibly enhances the fluorescence signal of the receptor via H-bonded complex formation with HSO4 − ions and co-ordinate complex formation with Hg 2+ ions.